BUZZ GROUP DALAM MENINGKATKAN PENGETAHUAN DAN SIKAP REMAJA DALAM PENCEGAHAN KEHAMILAN TIDAK DIINGINKAN (KTD) - Sofiana Salim; Abu Bakar; Retnayu Pradanie (Universitas Airlangga, 2014)
Unwanted pregnancy is unintended pregnancy by one or both prospective of infant’s parents. Lack of knowledgeabout process and prevention of pregnancy are the major cause of unwanted pregnancy on adolescents. This studyaimed to analyze buzz group effect on the adolescent’s knowledge and attitude about prevention of unwantedpregnancy at SMK Muhammadiyah 3 Tegaldlimo Banyuwangi.This study used quasi-experimental design and populationwere all of class X at SMK Muhammadiyah 3 Tegaldlimo Banyuwangi. The sampling used purposive sampling technique,based on inclusion criteria, 20 repondents consisted of 16 repondents as experiments group and 16 respondents ascontrol group. Data were collected by questionnaires and analyzed using Wilcoxon signed rank test and Mann Witney UTest with significant level α≤0,05. The results statistically showed that there were effect of buzz group onadolescent’s knowledge (p=0.001) and attitude (p=0.005). There was difference between experiment group andcontrol group after given buzz group on knowledge variable (p=0.000) and attitude variable (p=0.029). In conclusion, buzzgroup is an effective method of health education in providing information on prevention of unwanted preganancy inadolescent groups. Recommended for further research to analyze factors that effect adolescent’s knowledge andattitude about prevention of unwanted pregnancy and study the effect of buzz group on behavior on adolescents